ANALISIS KETERAMPILAN MENYIMAK CERITA SISWA KELAS III MI HIDAYATUSSIBYAN SUBANG - Putri Rahmatika, - (2023)
The background of this research is that there are children who have not been able to listen to stories properly, this can be seen from the students' ability to answer questions from a story they have listened to. Problems in listening activities also result in students having unsatisfactory grades. Therefore this study aims to determine students' listening skills, the inhibiting factors of listening skills and solutions to develop listening skills. This study uses a qualitative approach. The data collection techniques used by the authors are listening skill tests, interviews and observation. The research subjects were 10 students. There are inhibiting factors in understanding listening skills, namely the soft intonation of the teacher's voice so that it makes students easily sleepy and difficult to understand, soft intonation of voices so that it makes them sleepy, there are 4 solutions to improve listening skills, namely, choosing an interesting story, conditioning the class first, record important points, and use learning models listening to stories.